Carbon dioxide and methane fluxes from feeding and no-feeding mariculture ponds. (May 2016) - Chen, Yan; Dong, Shuanglin; Wang, Fang; Gao, Qinfeng; Tian, Xiangli
Abstract: The CO2 and CH4 fluxes at the water–air interface were measured in shrimp ( Marsupenaeus japonicus ) monoculture ponds (S) with feed supply and shrimp-sea cucumber ( Apostichopus japonicus ) polyculture ponds (SS) without feed supply. During farming seasons of the whole year, cumulated CO2 –C fluxes were −5.69 g m −2 (S) and 11.23 g m −2 (SS), respectively. The cumulated CO2 emissions from S and SS did not differ significantly. The cumulated CH4 –C emissions from S (0.57 g m −2 ) were significantly higher than those from SS (0.068 g m −2 ). S absorbed C from the atmosphere with a mean absorption rate of −5.12 g m −2, whereas SS emitted C to the atmosphere with a mean emission rate of 11.30 g m −2 . Over 20-year horizon, the compressive global warming potentials (cGWPs) were 33.55 (S) and 47.71 (SS), respectively, indicating both feeding and no-feeding mariculture ponds could promote global warming. Highlights: Seasonal variations of CO2 and CH4 fluxes from the mariculture ponds were studied. Both the feeding and no-feeding mariculture ponds promote the global warming. The mariculture ponds with feeding emit more CH4 than those without feeding.